2004
DOI: 10.1136/ip.2003.003376
|View full text |Cite
|
Sign up to set email alerts
|

Newspaper framing of fatal motor vehicle crashes in four Midwestern cities in the United States, 1999–2000

Abstract: Objective: To examine the public health messages conveyed by newspaper coverage of fatal motor vehicle crashes and determine the extent to which press coverage accurately reflects real risks and crash trends. Methods: Crash details were extracted from two years of newspaper coverage of fatal crashes in four Midwestern cities in the United States. Details and causal factors identified by reporters were compared to data from the National Highway Traffic Safety Administration's Fatality Analysis Reporting System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 16 publications
1
41
1
Order By: Relevance
“…Evidence for a particular over-representation of crashes with young people like suggested in Beullens et al (2008) and in Connor & Wesolowski (2004) was not found in the present data.…”
Section: Reporting Qualitycontrasting
confidence: 53%
See 2 more Smart Citations
“…Evidence for a particular over-representation of crashes with young people like suggested in Beullens et al (2008) and in Connor & Wesolowski (2004) was not found in the present data.…”
Section: Reporting Qualitycontrasting
confidence: 53%
“…They indicated that media seem to personalize and emotionalize traffic crashes, which might stress some aspects of crashes while neglecting others such as protective measures like seat belt wearing. Another instance of research on road crash framing is found in Connor & Wesolowski (2004) who published a study on the newspaper coverage of traffic crashes in four Midwestern cities in the United States. They made a comparison between newspapers and the official accident reporting system (FARS).…”
Section: Reporting Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] The article entitled "FarmRelated Injuries Among Old Order Anabaptist Children: Developing a Baseline From Which to Formulate and Assess Future Prevention Studies" uses a novel approach based on this methodology to obtain information about a difficult to reach study population. Data were obtained from three publications: a weekly newsletter, a biweekly newsletter, and a monthly publication.…”
mentioning
confidence: 99%
“…Other commentators (Connor & Wesolowski, 2004) have noted that newspapers presented fatal crashes as dramas with a victim/villain storyline; in keeping with this narrative strategy, newspapers were most likely to cover stories where a driver survived to take the blame. By highlighting crashes that diverge from the norm, focusing on the assignment of blame to a single party, and failing to convey the message that preventive practices such as seatbelt use increase odds for survival, newspapers remove crashes from a public health context and position them as individual issues.…”
Section: Priming Of Rtas In the Media In Kenyamentioning
confidence: 99%